Biblioteca digital para la Casa de la Cultura Ecuatoriana "Benjamín Carrión" de la ciudad de Latacunga. - Flores Pucuji, Silvana Pilar (2018)
The library of the Casa de la Culture Ecuadorian "Benjamin Carrion" core of Cotopaxi, located in the Canton Latacunga account with 5000 books' who are exposed to various risks such as: pollution of the books by bacteria and the possible eruption of the Cotopaxi volcano, added to this is the lack of security of the library in the event that you present some kind of threat. In order to conserve and preserve the fund bibliographic was presented the technological proposal of the creation of a digital library which aims to store books in digital format and made available to the public. For the development is worked with the SCRUM methodology with their respective phases what allowed divide in 6 modules the which they are distributed in the following way: 1) Authentication, 2) Manage profiles, 3) Manage collections, 4) Manage books, 5) Manage advertising and, 6) Generate reports. All has made possible the getting of a dynamic system which fulfills with the requirements specified by the client. In the web App 15 were centralized of which 5 are authorship of the Technical University of Cotopaxi, and 10 are part of the heritage of the library. Also it is important to mention that the App has an OCR system which is connected to the App, this software will be of optional use for some books which do not have copyrights.